Actual resuscitation actions after the training of chest compression-only CPR and AED use among new university students. (August 2019) - Nishiyama, Chika; Sato, Ryuhei; Baba, Masaaki; Kuroki, Hiroshi; Kawamura, Takashi; Kiguchi, Takeyuki; Kobayashi, Daisuke; Shimamoto, Tomonari; Koike, Kaoru; Tanaka, Shinsuke; Naito, Chisako; Iwami, Taku
Abstract: Background: Although cardiopulmonary resuscitation (CPR) training is recommended in schools, there are few attempts to train all students at universities and no reports showing actual resuscitation actions at emergency settings after the training. We surveyed how many students encountered a collapsed person, whether they performed any resuscitation actions, and any reasons why they could not do any resuscitation actions. Methods: We have provided chest compression-only CPR and automated external defibrillator (AED) use training for 3000 new university students every April since 2015 and followed up on their subsequent emergency actions to collapsed persons in the real world. We carried out a questionnaire survey for 2nd through 4th-year students during the annual student health checkup period in 2018. Results: A total of 7595 students underwent the annual health checkup and 5549 of them (73.1%) responded to the survey. The rates of encountering collapsed persons and out-of-hospital cardiac arrest (OHCA) patients were 2.5 and 1.1 per 100 person-years, respectively. Of the 264 students who encountered a collapsed person, 82 (53.6%) who encountered non-OHCA collapsed persons and 54 (48.6%) who encountered OHCA persons performed at least one resuscitation action including either chest compression, AED use, or any other various resuscitation actions. Conclusions: The incidence rate of encountering OHCA patients was 1.1 per 100 person-years and half of them who encountered a collapsed person performed at least one resuscitation action. Hands-on mass training would encourage university students to perform any resuscitation actions on the emergency scene.